Annual Plan 2007-08 - Planning Commission (Planning Commission, 2007)
The Eleventh Five Year Plan, which covers the period 2007-08 to 2011- 12, aims at faster and more inclusive growth. It targets faster growth in all productive sectors, agriculture, industry and services, with suitable interventions in policy. It seeks to achieve inclusiveness through significant improvements in literacy/education and health, greater employment opportunities and more focus on various socio-economic groups. Inclusive growth connotes a growth process, which yields broad based benefits and ensures equality of opportunity for all.
Planning Commission Government of India
Planning Commission Government of India